Voltage and pace-capture mapping of linear ablation lesions overestimates chronic ablation gap size. Issue 12 (26th April 2018) - O'Neill, Louisa; Harrison, James; Chubb, Henry; Whitaker, John; Mukherjee, Rahul K; Bloch, Lars Ølgaard; Andersen, Niels Peter; Dam, Høgni; Jensen, Henrik K; Niederer, Steven; Wright, Matthew; O'Neill, Mark; et al.
Abstract: Aims: Conducting gaps in lesion sets are a major reason for failure of ablation procedures. Voltage mapping and pace-capture have been proposed for intra-procedural identification of gaps. We aimed to compare gap size measured acutely and chronically post-ablation to macroscopic gap size in a porcine model. Methods and results: Intercaval linear ablation was performed in eight Göttingen minipigs with a deliberate gap of ∼5 mm left in the ablation line. Gap size was measured by interpolating ablation contact force values between ablation tags and thresholding at a low force cut-off of 5 g. Bipolar voltage mapping and pace-capture mapping along the length of the line were performed immediately, and at 2 months, post-ablation. Animals were euthanized and gap sizes were measured macroscopically. Voltage thresholds to define scar were determined by receiver operating characteristic analysis as <0.56 mV (acutely) and <0.62 mV (chronically). Taking the macroscopic gap size as gold standard, error in gap measurements were determined for voltage, pace-capture, and ablation contact force maps. All modalities overestimated chronic gap size, by 1.4 ± 2.0 mm (ablation contact force map), 5.1 ± 3.4 mm (pace-capture), and 9.5 ± 3.8 mm (voltage mapping). Error on ablation contact force map gap measurements were significantly less than for voltage mapping ( P = 0.003, Tukey's multiple comparisons test). Chronically, voltage mapping and pace-capture mapping overestimated macroscopic gap size by 11.9 ± 3.7 and 9.8 ± 3.5 mm, respectively. Conclusion: Bipolar voltage and pace-capture mapping overestimate the size of chronic gap formation in linear ablation lesions. The most accurate estimation of chronic gap size was achieved by analysis of catheter-myocardium contact force during ablation.